Composition, joining member and composite member
A tetrafluoroethylene polymer-based composition with specific metal oxide particles and antistatic agents addresses chargeability and thermal conductivity issues, offering improved adhesive and antistatic properties for semiconductor manufacturing components.
Patent Information
- Application Number
- JP2023104154
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-01-15
AI Technical Summary
Existing compositions containing tetrafluoroethylene polymers and metals or their oxides exhibit issues with chargeability and lack of thermal conductivity, plasma resistance, and antistatic properties, making them unsuitable for high-temperature semiconductor manufacturing applications.
A composition comprising particles of a tetrafluoroethylene polymer, metal or oxide particles with an average diameter of 10 μm or less, and an antistatic agent with specific cations, such as ammonium or imidazolium ions, is developed to enhance heat resistance, thermal conductivity, and antistatic properties.
The composition provides excellent adhesive properties, heat resistance, thermal conductivity, and antistatic properties, making it suitable for semiconductor manufacturing components like shower heads, electrostatic chucks, and CVD heaters.
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition containing particles of a tetrafluoroethylene-based polymer, a joining member made of the composition, and a composite member formed from the joining member. [Background technology]
[0002] Fluorine-based polymers, such as tetrafluoroethylene-based polymers, are excellent in heat resistance, mechanical properties, durability, and electrical properties (low dielectric constant, low dielectric tangent, etc.), and new materials endowed with these properties are being actively developed. For example, Patent Document 1 discloses a coating composition containing a fluorine-containing polymer containing a curable functional group, titanium dioxide, a flowability improver that is an associative acrylic polymer having an acid group and a base, and an organic solvent. Patent Document 2 discloses an antistatic release film having a fluororesin layer as the outermost layer and a resin layer containing an antistatic agent as the intermediate layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-12830 A [Patent Document 2] JP 2009-241388 A Summary of the Invention [Problem to be solved by the invention]
[0004] Compositions containing a tetrafluoroethylene polymer and a metal or its oxide have heat resistance and thermal conductivity, but have the problem of being easily charged. The coating composition of Patent Document 1 is said to be capable of forming a fluororesin layer with excellent ultraviolet shielding properties in the back sheet of a solar cell module, and the antistatic release film of Patent Document 2 is said to be excellent in releasability, cushioning properties, and antistatic properties, and can be suitably used when hot press bonding a flexible printed circuit board and a coverlay film. Meanwhile, in the semiconductor manufacturing process, susceptors, electrostatic chucks, vacuum chucks, ceramic heaters with built-in heaters, CVD heaters, and the like are used in semiconductor manufacturing equipment to place substrates such as silicon wafers, glass, and ceramics on the substrates. Such composite materials as parts for semiconductor manufacturing equipment are required to have heat resistance because they are exposed to high temperatures during use due to plasma irradiation, etc. In addition, for example, an electrostatic chuck uses electrostatic force to tightly contact a wafer and control the wafer temperature during etching, so the composite materials are required to have thermal conductivity and antistatic properties. The present inventors have found that a composition containing tetrafluoroethylene polymer particles, metal or oxide particles having a specific average particle size, and an antistatic agent containing a specific cation exhibits physical properties based on the tetrafluoroethylene polymer, and is excellent in antistatic properties and adhesive properties. They have also found that such a composition can be suitably used as a bonding member in the manufacture of a composite member as a part for semiconductor manufacturing, and have arrived at the present invention. An object of the present invention is to provide a composition which is excellent in heat resistance, thermal conductivity, plasma resistance, antistatic properties, and adhesion properties. [Means for solving the problem]
[0005] The present invention has the following aspects. [1] A composition comprising particles of a heat-fusible tetrafluoroethylene-based polymer, particles of a metal or an oxide thereof, and an antistatic agent, wherein the particles of the metal or the oxide thereof have an average particle size of 10 μm or less, and the antistatic agent comprises one or more nitrogen-containing cations selected from the group consisting of ammonium ions, imidazolium ions, pyrazolium ions, pyrazinium ions, pyridinium ions, pyridazinium ions, pyrimidinium ions, pyrrolidinium ions, piperidinium ions, quinolinium ions, and triazinium ions. [2] The composition according to [1], wherein the tetrafluoroethylene-based polymer comprises a heat-fusible tetrafluoroethylene-based polymer having an oxygen-containing polar group. [3] The composition according to [1] or [2], wherein the content of the tetrafluoroethylene-based polymer particles is 30% by mass or more. [4] The composition according to any one of [1] to [3], wherein the average particle size of the metal or oxide thereof is 50 nm or more and less than 1000 nm. [5] The BET specific surface area of the metal or oxide particles is 10 m 2 The composition according to any one of [1] to [4], wherein the composition is more than / g. [6] The composition according to any one of [1] to [5], wherein the particles of the metal or the oxide thereof are particles of a metal belonging to Group 3 or Group 4 or an oxide thereof. [7] The composition according to any one of [1] to [6], wherein the antistatic agent is a polymer-type antistatic agent containing a polyether ester amide block copolymer or an acrylic polymer having an oxyalkylene skeleton in its molecular chain. [8] The composition according to any one of [1] to [7], further comprising a solvent. [9] The composition according to [8], wherein the solvent is at least one selected from the group consisting of water, amides, ketones and esters.
[10] Any of the compositions according to [1] to [9], which is used as a joining member.
[11] A joining member comprising the composition according to any one of [1] to
[10] .
[12] A composite member comprising a first member having a surface made of ceramics, a second member having a surface made of metal, and a bonding layer bonding the ceramic surface of the first member to the metal surface of the second member, a composite member, wherein the bonding layer comprises particles of a tetrafluoroethylene-based polymer, particles of a metal or an oxide thereof, and an antistatic agent, the particles of the metal or the oxide thereof having an average particle size of 10 μm or less, and the antistatic agent comprises one or more nitrogen-atom-containing cations selected from the group consisting of ammonium ions, imidazolium ions, pyrazolium ions, pyrazinium ions, pyridinium ions, pyridazinium ions, pyrimidinium ions, pyrrolidinium ions, piperidinium ions, quinolinium ions, and triazinium ions.
[13] A composite member according to
[12] , which is a component for semiconductor manufacturing.
[14] The composite member according to
[13] , wherein the semiconductor manufacturing part is a shower head, an electrostatic chuck, a vacuum chuck, or a CVD heater. Effect of the Invention
[0006] According to the present invention, there is provided a composition having excellent heat resistance, thermal conductivity, plasma resistance, antistatic properties, and adhesive properties. The composition of the present invention can be suitably used as a joining member, and can be used to prepare a composite member having excellent heat resistance, vacuum resistance, antistatic properties, etc., and applicable to parts for semiconductor manufacturing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The following terms have the following meanings: "Average particle size (D50)" is the cumulative 50% volumetric diameter of a particle or filler determined by a laser diffraction / scattering method. In other words, the particle size distribution is measured by a laser diffraction / scattering method, the total volume of the particle or filler group is set as 100%, a cumulative curve is calculated, and the particle size is the point on the cumulative curve where the cumulative volume is 50%. The D50 of particles or fillers is determined by dispersing the particles or fillers in water and analyzing them by a laser diffraction / scattering method using a laser diffraction / scattering type particle size distribution measuring device (LA-920 measuring device, manufactured by Horiba, Ltd.). "Melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). "Glass transition temperature (Tg)" is a value measured by analyzing a polymer using the dynamic mechanical analysis (DMA) method. The "viscosity" is determined by measuring the composition using a Brookfield viscometer at 25° C. and 30 rpm. The measurement is repeated three times, and the average value of the three measured values is calculated. The "thixotropy ratio" is a value calculated by dividing the viscosity η1 of the composition measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement is repeated three times, and the average value of the three measured values is used. The term "unit" in a polymer means an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit formed directly by a polymerization reaction, or may be a unit in which a part of the unit is converted into a different structure by processing the polymer. Hereinafter, a unit based on monomer a is also referred to simply as a "monomer a unit."
[0008] The composition of the present invention (hereinafter also referred to as "the composition") contains particles (hereinafter also referred to as "F particles") of a heat-fusible tetrafluoroethylene polymer (hereinafter also referred to as "F polymer"), particles of a metal or an oxide thereof, and an antistatic agent, wherein the average particle size of the particles of the metal or an oxide thereof is 10 μm or less, and the antistatic agent contains one or more nitrogen-containing cations selected from the group consisting of ammonium ions, imidazolium ions, pyrazolium ions, pyrazinium ions, pyridinium ions, pyridazinium ions, pyrimidinium ions, pyrrolidinium ions, piperidinium ions, quinolinium ions, and triazinium ions. This composition has excellent mechanical properties, heat resistance, and electrical properties (low linear expansion coefficient, low dielectric constant, and low dielectric tangent) based on the F polymer, and also has excellent antistatic properties and adhesive properties.
[0009] In the present composition, the antistatic agent containing a specific nitrogen atom-containing cation is likely to be adsorbed to the surface of metal or oxide particles having a small average particle size, suppressing their aggregation while improving the affinity with the F polymer, and is therefore presumably improving the uniform dispersibility of the present composition. Therefore, when the composition is used as a bonding material, particularly as a bonding material for composite materials for semiconductor manufacturing parts, a matrix structure containing an F polymer with high antistatic properties is easily formed as a bonding layer that contacts a member having a ceramic or metal surface. As a result, it is presumed that a composite material with excellent antistatic properties is obtained, with improved heat resistance, electrical properties, etc. based on the F polymer and improved adhesion. This effect is more pronounced when the composition contains specific F particles, which will be described later.
[0010] In the present composition, the F polymer is a heat-meltable polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE units"). Here, the heat-meltable polymer means a polymer having a temperature at which the melt flow rate is 1 to 1000 g / 10 min under a load of 49 N. The melting temperature of the F polymer is preferably 200° C. or higher, more preferably 260° C. or higher. The melting temperature of the F polymer is preferably 325° C. or lower, more preferably 320° C. or lower. The F polymer may be used alone or in combination of two or more kinds.
[0011] The glass transition temperature of the F polymer is preferably 60° C. or higher, more preferably 75° C. or higher. The glass transition temperature of the F polymer is preferably 120° C. or lower, more preferably 100° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a droplet of a mixture for wetting tension testing (manufactured by Wako Pure Chemical Industries, Ltd.) specified in JIS K 6768 on a flat plate made of the F polymer.
[0012] F polymers include polytetrafluoroethylene (PTFE), polymers containing TFE units and units based on ethylene (ETFE), polymers containing TFE units and units based on propylene, polymers containing TFE units and units based on perfluoro(alkyl vinyl ether) (PAVE) (PAVE units) (PFA), and polymers containing TFE units and units based on hexafluoropropylene (FEP). F polymers are preferably PFA or FEP, and more preferably PFA. These polymers may further contain units based on other comonomers. PAVE is preferably CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF2CF3 (hereinafter also referred to as "PPVE"), and more preferably PPVE.
[0013] At least one of the F polymers preferably has an oxygen-containing polar group, more preferably has a hydroxyl group-containing group or a carbonyl group-containing group, and even more preferably has a carbonyl group-containing group. In this case, when the composition is used as a bonding member, it is likely to have excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric tangent), and further excellent adhesiveness. The hydroxyl-containing group is preferably a group containing an alcoholic hydroxyl group, more preferably -CF2CH2OH or -C(CF3)2OH. The carbonyl group-containing group is preferably a carboxyl group, an alkoxycarbonyl group, an amide group, an isocyanate group, a carbamate group (-OC(O)NH2), an acid anhydride residue (-C(O)OC(O)-), an imide residue (-C(O)NHC(O)-, etc.), a formyl group, a halogenoformyl group, a urethane group (-NHC(O)O-), a carbamoyl group (-C(O)-NH2), a ureido group (-NH-C(O)-NH2), an oxamoyl group (-NH-C(O)-C(O)-NH2) or a carbonate group (-OC(O)O-), and more preferably an acid anhydride residue. When the F polymer has an oxygen-containing polar group, the number of oxygen-containing polar groups in the F polymer is 1×10 6The number of oxygen-containing polar groups per unit is preferably 10 to 5000, more preferably 100 to 3000. The number of oxygen-containing polar groups in the F polymer can be quantified by the composition of the polymer or the method described in WO 2020 / 145133.
[0014] The oxygen-containing polar group may be contained in a unit based on a monomer in the F polymer, or may be contained in a terminal group of the main chain of the F polymer, the former being preferred. The latter embodiment includes an F polymer having an oxygen-containing polar group as a terminal group derived from a polymerization initiator, a chain transfer agent, etc., and an F polymer obtained by subjecting an F polymer to plasma treatment or ionizing radiation treatment.
[0015] The heat-fusible F polymer is preferably a polymer (1) that contains TFE units and PAVE units and contains 2.0 to 5.0 mol% of PAVE units based on the total units and does not have an oxygen-containing polar group, or a polymer (2) that contains TFE units and PAVE units and has an oxygen-containing polar group. When such an F polymer is used, spherulites with a relatively small radius are easily formed. Therefore, the adhesiveness is easily improved when the composition is used as a joining member.
[0016] It is more preferable that the polymer (1) is composed only of TFE units and PAVE units, and contains more than 2.5 mol % and 5.0 mol % or less of PAVE units based on the total units. In addition, the fact that the polymer (1) does not have an oxygen-containing polar group means that the number of the oxygen-containing polar groups is 1×10 of the carbon atoms constituting the polymer main chain. 6 This means that the number of oxygen-containing polar groups in the polymer is less than 500 per unit. The number of the oxygen-containing polar groups is preferably 100 or less, more preferably less than 50. The lower limit of the number of the oxygen-containing polar groups is 1. The polymer (1) may be produced by using a polymerization initiator or a chain transfer agent that does not generate an oxygen-containing polar group as a terminal group of the polymer chain, or by fluorinating an F polymer having an oxygen-containing polar group (such as an F polymer having an oxygen-containing polar group derived from a polymerization initiator at the terminal group of the polymer main chain). Examples of the fluorination method include a method using fluorine gas (see JP 2019-194314 A, etc.).
[0017] The polymer (2) is preferably a heat-meltable F polymer having a carbonyl group-containing group containing TFE units and PAVE units, more preferably a polymer containing TFE units, PAVE units, and units based on a monomer having a carbonyl group-containing group, and containing these units in this order in an amount of 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol% relative to the total units. Specific examples of such F polymers include the polymers described in WO 2018 / 16644. The monomer having a carbonyl group-containing group is preferably itaconic anhydride, citraconic anhydride, or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), and more preferably NAH.
[0018] In this composition, the F polymer may be a mixture of particles of polytetrafluoroethylene (PTFE) and particles of a heat-fusible F polymer having oxygen-containing polar groups. In this case, from the viewpoint of excellent adhesiveness and heat resistance, the content of PTFE particles in the mixture of PTFE particles and particles of a heat-fusible F polymer having an oxygen-containing polar group is preferably 50 to 90 mass %.
[0019] The F particles preferably have an average particle size (D50) of 0.3 μm or more and less than 10 μm. The D50 of the F particles is preferably 0.5 μm or more, more preferably 1.0 μm or more. The D50 of the F particles is preferably less than 10 μm, more preferably 8 μm or less. In this case, the composition is likely to have excellent dispersibility and processability, and is likely to have excellent physical properties such as heat resistance, electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric tangent), and adhesiveness when used as a joining member. The F particles are particles containing an F polymer, and preferably consist of an F polymer. One type of F particle may be used, or two or more types of F particles may be used. When two or more kinds of F particles are used, it is preferable that the F particles are a mixture of PTFE particles and particles of a heat-fusible F polymer having an oxygen-containing polar group. In order to provide the composition with excellent adhesiveness and heat resistance, it is preferable that the content of the PTFE particles in the mixture of PTFE particles and particles of a heat-fusible F polymer having an oxygen-containing polar group is 50 to 90 mass%.
[0020] In the present composition, the content of the F particles is preferably 20% by mass or more, and more preferably 30% by mass or more. The content may be 70% by mass or less, or may be 50% by mass or less.
[0021] The average particle size of the metal or its oxide particles contained in the composition is 10 μm or less. The shape of the particles may be various shapes such as spherical, cubic, octahedral, plate-like, scaly, rod-like, columnar, cone-like, frustum-like, polyhedral, hollow, etc. Among them, spherical is preferable. The average particle size of the metal or its oxide particles is preferably 5 μm or less, more preferably 2 μm or less, and even more preferably less than 1000 nm. The average particle size of the metal or its oxide particles is preferably 50 nm or more. When the average particle size of the metal or its oxide particles is within the above range, the antistatic agent described below is easily adsorbed on the surface of the particles. In particular, in the present composition which is in a liquid state (dispersion state) described below, it is presumed that the polymer chains suitably possessed by the antistatic agent are associated in the solvent by hydrogen bonds or electrical interactions, thereby suppressing the aggregation of the metal or its oxide particles and further improving the dispersibility in the present composition, and the thermal conductivity and antistatic properties are more likely to be improved.
[0022] The specific surface area of the metal or oxide particles by the BET method is set to 10 m from the viewpoint of making it easier for the antistatic agent described later to be adsorbed to the surface of the particles, suppressing particle aggregation and improving stability, and from the viewpoint of making it easier to capture radicals and suppressing deterioration of the F polymer. 2 / g, and preferably more than 40m 2 The specific surface area of the metal or oxide particles according to the BET method is preferably more than 100 m 2 It is preferable that the molecular weight is not more than 1 / g. The specific surface area measured by the BET method is the average value of measurements taken three times by the BET flow method (single point method) in a mixed gas atmosphere of helium and nitrogen after degassing metal or oxide particles at 100°C for 60 minutes. The content of the metal or oxide particles in the present composition is preferably within the range of 10 to 70% by mass relative to the F polymer, in which case the dispersibility of the metal or oxide particles in the present composition is likely to be excellent.
[0023] Examples of metal particles include particles of silver, copper, aluminum, nickel, iron, lead, titanium, molybdenum, tantalum, niobium, gold, platinum, and the like. Examples of metal oxide particles include particles of aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, zirconium oxide, tin oxide, antimony oxide, zinc antimonate, indium oxide, tin-doped indium oxide (ITO), copper oxide, iron oxide, and silver oxide.
[0024] The particles of metal or its oxide are preferably particles of metal or its oxide belonging to Group 3 or Group 4, such as scandium, yttrium, lanthanum, cerium, titanium, zirconium, hafnium, etc. Among them, oxides of metals belonging to Group 3 or Group 4 are more preferable, and titanium dioxide is even more preferable. These metal oxides are easy to capture radicals and easily exert the effect of suppressing the deterioration of the F polymer. The titanium dioxide may be of the rutile type, anatase type, or the like, with the rutile type being preferred from the viewpoint of weather resistance. Commercially available titanium dioxide products may be used.
[0025] The particles of metal or its oxide may be surface-treated. For example, in the case of titanium dioxide, at least a part of the surface may be coated with alumina, silica, zirconia, or the like, or may be surface-treated with a silane coupling agent, an organic siloxane, a polyol, an alkylamine, or the like.
[0026] The antistatic agent contained in the present composition contains one or more nitrogen-containing cations selected from the group consisting of ammonium ion, imidazolium ion, pyrazolium ion, pyrazinium ion, pyridinium ion, pyridazinium ion, pyrimidinium ion, pyrrolidinium ion, piperidinium ion, quinolinium ion, and triazinium ion. These nitrogen-containing cations may have an alkyl group having 1 to 10 carbon atoms, which may contain an etheric oxygen atom, on the nitrogen atom. In addition, these nitrogen-containing cations may have a carbon atom-fluorine atom bond, and examples of such nitrogen-containing cations include those in which a polyfluoroalkyl group, which may contain an etheric oxygen atom, is bonded to the nitrogen atom of the nitrogen-containing cation.
[0027] Among them, the antistatic agent is preferably a polymer type, and more preferably a polymer type antistatic agent containing a polyether / polyolefin block copolymer, a polyetheresteramide block copolymer, or an acrylic polymer having a (poly)oxyalkylene skeleton in its molecular chain. The nitrogen atom-containing cation may be present at the main chain end or side chain end of these polymers, or may be included in these polymers. The use of such an antistatic agent not only provides excellent antistatic properties, but also makes it easier for the agent to be adsorbed onto the surfaces of metal or oxide thereof particles in the composition. In particular, in the composition in the form of a liquid (dispersion) described below, it is presumed that the polymer chains of the antistatic agent associate in the solvent through hydrogen bonds or electrical interactions, thereby suppressing aggregation of the metal or oxide thereof particles and improving stability. In this specification, the term "acrylic polymer" refers to a (meth)acrylic polymer containing a (meth)acrylic monomer as its main constituent unit. Examples of the (meth)acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, and cyclohexyl (meth)acrylate. "(Meth)acrylic" is a general term for acrylic, methacrylic, and both, and "(meth)acrylate" is a general term for acrylate, methacrylate, and both.
[0028] In the present composition, the content of the antistatic agent is preferably 5 to 50 mass % and more preferably 10 to 30 mass % based on the metal or oxide particles, from the viewpoint of exhibiting good properties such as heat resistance, antistatic properties, thermal conductivity, and adhesiveness. As the antistatic agent, a commercially available product can be used.
[0029] In addition, the composition may further contain other antistatic agents, which are conductive polymers such as polyaniline, polyacetylene, polyparaphenylene, polypyrrole, polythiophene, and polyvinylcarbazole, as long as the effects of the present invention are not impaired.
[0030] The present composition may further contain another resin different from the F polymer, as long as the effect of the present invention is not impaired. Such another resin may be contained in the present composition as non-hollow particles, and when the present composition further contains a solvent described below, the other resin may be dissolved or dispersed in the solvent constituting the present composition. Examples of the other resins include polyester resins such as liquid crystalline aromatic polyesters, polyimide resins, polyamideimide resins, epoxy resins, maleimide resins, urethane resins, polyphenylene ether resins, polyphenylene oxide resins, and polyphenylene sulfide resins. Among these, aromatic polyimides or precursors thereof are preferred, and at least one polyimide or precursor thereof selected from the group consisting of aromatic polyimides, aromatic polyamic acids, aromatic polyamideimides, and precursors of aromatic polyamideimides is more preferred. The polyimide or a precursor thereof is preferably contained in the present composition as a varnish dissolved in a dispersion medium. When the present composition further contains another resin, the content thereof relative to the F particles is preferably 1 to 25% by mass.
[0031] The composition may further contain other inorganic fillers other than the above-mentioned metal or oxide particles thereof, within the scope of not impairing the effects of the present invention. Examples of such other inorganic fillers include silica (crystalline silica, fused silica, spherical fused silica, etc.), wollastonite, talc, mica, silicon nitride, silicon carbide, calcium silicate, mica, boron nitride, aluminum nitride, calcium carbonate, potassium titanate, aluminum hydroxide, magnesium hydroxide, aluminum borate, barium sulfate, carbon black, graphite, carbon nanotubes, montmorillonite, boehmite, kaolin, smectite, zonolite, verculite, sericite, etc. The other inorganic fillers may be used alone or in combination of two or more kinds.
[0032] The composition may be in a powder form or in a liquid form further containing a solvent. From the viewpoint of easy handling, the composition is preferably in a dispersion form further containing a solvent. The solvent is preferably a compound that is liquid at 25° C. under atmospheric pressure and has a boiling point of 50 to 240° C. One type of solvent may be used, or two or more types may be used. When two types of solvents are used, the two types of solvents are preferably compatible with each other. The solvent is preferably at least one selected from the group consisting of water, amides, ketones and esters. Examples of amides include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropanamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N,N-diethylformamide, hexamethylphosphoric triamide, and 1,3-dimethyl-2-imidazolidinone. Examples of the ketone include acetone, methyl ethyl ketone, methyl isopropyl ketone, methyl isobutyl ketone, methyl n-pentyl ketone, methyl isopentyl ketone, 2-heptanone, cyclopentanone, cyclohexanone, and cycloheptanone. Examples of the ester include methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, methyl pyruvate, ethyl pyruvate, methyl methoxypropionate, ethyl ethoxypropionate, ethyl 3-ethoxypropionate, γ-butyrolactone, and γ-valerolactone.
[0033] When the composition contains a solvent, the content of the solvent is preferably 40% by volume or more, more preferably 60% by volume or more, based on the total volume of the composition, and is preferably 90% by volume or less, more preferably 80% by volume or less. When the composition contains a solvent, the solid content concentration in the composition is preferably 20% by volume or more, more preferably 40% by volume or more. The solid content concentration is preferably 80% by volume or less, more preferably 70% by volume or less. The solid content means the total amount of substances that form the solid content in the molded product formed from the composition. Specifically, F particles and metal or oxide particles thereof are solid content, and when the composition contains other resins or other inorganic fillers, the other resins and other inorganic fillers are also solid content, and the total volume concentration of these components is the solid content concentration in the composition.
[0034] When the composition contains a solvent, the composition may further contain a surfactant. The surfactant is preferably a nonionic surfactant. Examples of the nonionic surfactant include glycol surfactants, acetylene surfactants, silicone surfactants, and fluorine surfactants.
[0035] The present composition may further contain additives such as a thixotropic agent, a viscosity modifier, an antifoaming agent, a dehydrating agent, a plasticizer, a weather resistance agent, an antioxidant, a heat stabilizer, a lubricant, an antistatic agent, a whitening agent, a colorant, a conductive agent, a release agent, and a flame retardant.
[0036] When the composition contains a solvent and is liquid, the content of F particles in the liquid composition is preferably 25% by mass or more, more preferably 30% by mass or more, and is preferably 75% by mass or less, more preferably 60% by mass or less. When the composition contains a solvent and is liquid, the viscosity is preferably 10 mPa·s or more, more preferably 100 mPa·s or more. The viscosity of the liquid composition is preferably 10,000 mPa·s or less, more preferably 3,000 mPa·s or less. In this case, the composition has excellent coatability and is easy to form a bonding layer of any thickness. In addition, the composition having a viscosity in this range is easy to highly express the physical properties of the F polymer in the bonding layer formed therefrom. When the present composition contains a liquid dispersion medium and is in a liquid state, the thixotropy ratio is preferably from 1.0 to 3.0.
[0037] The composition can be obtained by mixing F particles, metal or oxide particles, the above-mentioned antistatic agent, and, if necessary, a solvent, other resins, other inorganic fillers, surfactants, additives, etc. There is no particular restriction on the order of mixing, and the mixing method may be either lump mixing or multiple separate mixings. Mixing devices for obtaining the present composition include stirring devices equipped with blades, such as a Henschel mixer, a pressure kneader, a Banbury mixer, and a planetary mixer; grinding devices equipped with media, such as a ball mill, an attritor, a basket mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a spike mill, and an agitator mill; and dispersing devices equipped with other mechanisms, such as a microfluidizer, a nanomizer, an ultimizer, an ultrasonic homogenizer, a dissolver, a disperser, a high-speed impeller, a thin film swirling high-speed mixer, a planetary stirrer, and a V-type mixer.
[0038] The present composition can be suitably used as a bonding member. That is, one aspect of the present invention is a bonding member made of the present composition (hereinafter, referred to as the present bonding member). The present joining member is useful as a joining member when forming a composite member, and is particularly useful as a joining or adhesive member for a composite member that constitutes a part or all of a part for semiconductor manufacturing. In other words, the present joining member is also an adhesive member.
[0039] The present invention also provides a composite member comprising a first member having a surface made of ceramic, a second member having a surface made of metal, and a bonding layer bonding the ceramic surface of the first member and the metal surface of the second member, The bonding layer comprises tetrafluoroethylene polymer particles, metal or oxide particles, and an antistatic agent, the metal or oxide particles having an average particle size of 10 μm or less, and the antistatic agent comprises one or more nitrogen-containing cations selected from the group consisting of ammonium ions, imidazolium ions, pyrazolium ions, pyrazinium ions, pyridinium ions, pyridazinium ions, pyrimidinium ions, pyrrolidinium ions, piperidinium ions, quinolinium ions, and triazinium ions (hereinafter also referred to as "the present composite material"). The bonding layer in the composite member is preferably formed by the bonding member. The first member of the composite member has a surface made of ceramics, which includes glass, and the second member of the composite member has a surface made of metal, such as copper or aluminum. The composite member preferably constitutes a part or the whole of a semiconductor manufacturing part, such as a shower head, an electrostatic chuck, a vacuum chuck, or a CVD heater. The electrostatic chuck includes a ceramic substrate, a metal substrate, and a bonding layer that bonds them together, and has a function of fixing a semiconductor wafer.
[0040] The present composite member can be manufactured, for example, as follows. First, the present bonding member is applied to the ceramic surface of the first member to form a coating layer made of the present bonding member. Coating methods for the present bonding member include a coating method, a droplet ejection method, and a dipping method. Next, the first member having the coating layer is heated to bake the F polymer. The heating is preferably performed in a temperature range equal to or higher than the melting temperature of the F polymer, specifically, at 340 to 400°C for 0.1 to 30 minutes. When the present bonding member is made of the present composition further containing a solvent, it is preferable to first perform a preliminary heating to remove the solvent. The heating device may be an oven or a ventilation drying furnace. The heat source in the heating device may be a contact type heat source such as hot air or a hot plate, or a non-contact type heat source such as infrared rays. The heating may be performed under atmospheric pressure or under reduced pressure, and the heating atmosphere may be either an air atmosphere or an inert gas atmosphere (helium gas, neon gas, argon gas, nitrogen gas, etc.). In this manner, a bonding layer made of the bonding member containing the F polymer is formed on the ceramic surface of the first member. Next, the metal surface of the second member is placed on the surface of the bonding layer as a lamination surface, and laminated by heat pressing to obtain the present composite member. The heat pressing temperature is preferably equal to or lower than the melting point of the F polymer, more preferably 120 to 300°C, and even more preferably 140 to 240°C. When the heat pressing temperature is within the above range, the first member and the second member can be bonded while suppressing thermal deterioration, and peeling at the interface between the bonding layer and the first member, or between the bonding layer and the second member, is likely to be suppressed. In the above, the present bonding material may be applied to the metal surface of the second component, heated to form a bonding layer, and the ceramic surface of the first component may be placed on the bonding layer and laminated to produce the present composite component.
[0041] In addition, the present bonding material may be applied to the ceramic surface of a first member and the metallic surface of a second member, heated to form a bonding layer, and then laminated together with the bonding layer surfaces of both members to produce the present composite member. Furthermore, a joining sheet may be created from this joining member, and the joining sheet may be placed between the ceramic surface of the first member and the metal surface of the second member, and laminated by heat pressing or the like to produce this composite member. Alternatively, the present composite member may be produced by coating the present joining member on the ceramic surface of a first component and then bonding the metallic surface of a second component to the coated surface, or by coating the present joining member on the metallic surface of a second component and then bonding the ceramic surface of a first component to the coated surface.
[0042] In the present composite member, the absolute value of the linear expansion coefficient of the bonding layer formed from the present bonding member is preferably 30 ppm / °C or less, more preferably 15 ppm / °C or less. In this case, peeling at the interface between the bonding layer and the first member or between the bonding layer and the second member in the present composite member is easily suppressed. The lower limit of the absolute value of the linear expansion coefficient of the bonding layer is 0 ppm / °C. In the present composite member, the peel strength between the bonding layer and the first member, and between the bonding layer and the second member is preferably 10 N / cm or more, more preferably 15 N / cm or more, and is preferably 100 N / cm or less.
[0043] Although the present composition, the present joining member, and the present composite member have been described above, the present invention is not limited to the configurations of the above-mentioned embodiments. For example, the present composition, the present joining member, and the present composite member may have any other configuration in addition to the configurations of the above-mentioned embodiments, or may be replaced with any configuration that produces a similar effect. EXAMPLES
[0044] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. 1. Preparation of each ingredient [F Polymer] F particle 1: containing 97.9 mol%, 0.1 mol%, and 2.0 mol% of TFE units, NAH units, and PPVE units, in that order, and having a carbonyl group-containing group with a main chain carbon number of 1×10 6 Tetrafluoroethylene polymer particles (melting temperature: 300°C) with 1000 particles per particle (D50: 2.4 μm, specific surface area: 9 m 2 / g) [Metal or oxide particles] Metal oxide 1: Spherical titanium dioxide with an average particle size of 0.4 μm Metal oxide 2: Spherical titanium dioxide with an average particle size of 10.6 μm [Antistatic agent] Agent 1: 1-Ethyl-3-methylimidazolium ethyl sulfate
[0045] 2. Preparation of the composition [Production Example 1] Using a centrifugal mixer, F particles 1, metal oxide 1, agent 1 and water were mixed to produce liquid composition 1 having an F particle 1 content of 30 mass%, a metal oxide 1 content of 15 mass% and an agent 1 content of 5 mass%. [Production Example 2] Using a centrifugal mixer, F particles 1, metal oxide 2, agent 1 and water were mixed to produce liquid composition 2 having an F particle 1 content of 30 mass%, a metal oxide 2 content of 15 mass% and an agent 1 content of 5 mass%. [Production Example 3] The same operation as in Production Example 1 was carried out except that Agent 1 was not added, to produce Liquid Composition 3 having an F Particle 1 content of 30 mass % and a Metal Oxide 1 content of 15 mass %.
[0046] 3. Creation and evaluation of composite materials 3-1. Creating composite members for evaluation [Example 1] The liquid composition 1 obtained according to Production Example 1 was applied to one surface of an aluminum plate (length 130 mm, width 130 mm, thickness 0.3 mm; A6061P-T6) using a die coater, passed through a ventilated drying oven (oven temperature 150°C) for 3 minutes to remove water and form a dry film, and then passed through a far-infrared oven at a furnace temperature of 350°C for 5 minutes to melt and sinter the F particles 1, forming a bonding layer (thickness 300 μm) containing an F polymer on the surface of the aluminum plate. A glass plate (length 110 mm, width 110 mm, thickness 1.1 mm; float glass) was placed on the surface of this bonding layer and hot-pressed to produce a composite member 1. [Examples 2-3] Composite materials 2 and 3 were obtained by carrying out the same procedure as in Example 1, except that Liquid composition 2 or Liquid composition 3 was used instead of Liquid composition 1.
[0047] 3-2. Heat resistance Each composite member was heated in a vacuum atmosphere at 160°C for 24 hours, and the presence or absence of peeling or swelling of the composite member after heating was visually evaluated. Neither peeling nor swelling was observed for Composite Member 1 and Composite Member 3. On the other hand, peeling and swelling were observed for Composite Member 2.
[0048] 3-3. Antistatic properties (surface resistivity) Composite material 1 and composite material 3, which showed no peeling or swelling after heating at 160°C for 24 hours, were subjected to surface resistivity measurement using a microcurrent meter (8340A) and a resistivity chamber in accordance with JIS C 2151. The surface resistivity of composite material 1 was 10 8 Ω / □, the surface resistivity of composite material 3 is 10 10 Ω / □, and the composite material 1 had antistatic properties. [Industrial Applicability]
[0049] The composition of the present invention is excellent in heat resistance, thermal conductivity, plasma resistance, and antistatic properties, and also has excellent adhesive properties. Therefore, the composition of the present invention can be suitably used as a joining member for semiconductor manufacturing equipment members, and can be used to prepare composite members that are excellent in heat resistance, vacuum resistance, and antistatic properties, such as shower heads, electrostatic chucks, vacuum chucks, and CVD heaters, which are semiconductor manufacturing parts.
Claims
1. A composition comprising particles of a heat-fusible tetrafluoroethylene-based polymer, particles of a metal or an oxide thereof, and an antistatic agent, wherein the particles of the metal or the oxide thereof have an average particle size of 10 μm or less, and the antistatic agent comprises one or more nitrogen-atom-containing cations selected from the group consisting of ammonium ions, imidazolium ions, pyrazolium ions, pyrazinium ions, pyridinium ions, pyridazinium ions, pyrimidinium ions, pyrrolidinium ions, piperidinium ions, quinolinium ions, and triazinium ions.
2. 2. The composition of claim 1, wherein the tetrafluoroethylene-based polymer comprises a heat-fusible tetrafluoroethylene-based polymer having oxygen-containing polar groups.
3. The composition according to claim 1 , wherein the content of the tetrafluoroethylene-based polymer particles is 30% by mass or more.
4. The composition according to claim 1 , wherein the average particle size of the metal or oxide thereof is 50 nm or more and less than 1000 nm.
5. The BET specific surface area of the metal or oxide particles is 10 m 2 The composition of claim 1 , wherein the molecular weight is greater than 1 / g.
6. 2. The composition according to claim 1, wherein the particles of a metal or an oxide thereof are particles of a metal or an oxide thereof belonging to Group 3 or Group 4.
7. The composition according to claim 1 , wherein the antistatic agent is a polymer-type antistatic agent comprising a polyetheresteramide block copolymer or an acrylic polymer having an oxyalkylene skeleton in its molecular chain.
8. The composition of claim 1 further comprising a solvent.
9. The composition according to claim 8, wherein the solvent is at least one selected from the group consisting of water, amides, ketones and esters.
10. The composition according to claim 1 , which is used as a joining material.
11. A joining member comprising the composition according to any one of claims 1 to 10.
12. A composite member comprising a first member having a surface made of ceramics, a second member having a surface made of metal, and a bonding layer bonding the ceramic surface of the first member and the metal surface of the second member, a composite member, wherein the bonding layer comprises particles of a tetrafluoroethylene-based polymer, particles of a metal or an oxide thereof, and an antistatic agent, the particles of the metal or the oxide thereof having an average particle size of 10 μm or less, and the antistatic agent comprises one or more nitrogen-atom-containing cations selected from the group consisting of ammonium ions, imidazolium ions, pyrazolium ions, pyrazinium ions, pyridinium ions, pyridazinium ions, pyrimidinium ions, pyrrolidinium ions, piperidinium ions, quinolinium ions, and triazinium ions.
13. The composite member of claim 12 which is a component for semiconductor manufacturing.
14. 14. The composite member of claim 13, wherein the semiconductor manufacturing part is a showerhead, an electrostatic chuck, a vacuum chuck, or a CVD heater.
Citation Information
Patent Citations
Antistatic release film
JP2009241388A
Coating material composition, backside sheet for solar cell module, and solar cell module
JP2014012830A